Association of history of allergies and influenza-like infections with laryngeal cancer in a case-control study - Filippidis, Filippos; Becker, Nikolaus; Dyckhoff, Gerhard; Kirschfink, Michael; Becher, Heiko; Ramroth, Heribert (European archives of oto-rhino-laryngology and head & neck, 2015)
Prior studies suggest that history of allergy and infections early in life might be inversely associated with cancer. We explored the association between allergies, recent influenza infections and laryngeal cancer risk. We used data from a case-control study which included 229 cases of laryngeal cancer and 769 population controls matched for age and sex. History of a physician-diagnosed allergy, influenza-like infections in the past 5 years, smoking, alcohol consumption and occupational exposure to carcinogens were self-reported. Allergies were classified into two groups (Type I and Type IV), according to the underlying immunologic mechanism. Conditional logistic regression models were fitted using laryngeal cancer as the outcome, adjusting for smoking, alcohol consumption and occupational exposure and stratified for age and sex. Having any allergy was not associated significantly with laryngeal cancer. Although Type I and Type IV allergies were non-significantly associated with laryngeal cancer, Type IV allergies showed a strong inverse association after adjusting for smoking and alcohol (OR 0.50, 95 % CI 0.22-1.2). Participants who reported at least one influenza-like infection during the past 5 years were significantly less likely to have laryngeal cancer (OR 0.57, 95 % CI 0.39-0.81). After considering fever (≥38.5 °C) as a criterion for influenza infection, the association between influenza infection and laryngeal cancer was even stronger (OR 0.29, 95 % CI 0.13-0.63). We found no significant association between any allergy and laryngeal cancer, some indication of an inverse association between Type IV allergy and laryngeal cancer, whereas recent influenza infections were inversely associated with laryngeal cancer risk.
Gesehen am 03.08.2021